A monomolecular platform with varying gated photochromism. Issue 69 (19th November 2020) - Li, Yuezheng; Chen, Xuanying; Weng, Taoyu; Yang, Jufang; Zhao, Chunrui; Wu, Bin; Zhang, Man; Zhu, Liangliang; Zou, Qi
Abstract : A strategy to realize varying degrees of gated photochromic properties by coordinating with different metal ions within one unimolecular system was devised to achieve the construction of a logic circuit for multi-functional molecular switching. Abstract : In the development of modern high-performance photoelectric materials, the gated photochromic materials have attracted wide attention. However, the integration of varying signal regulations into gated photochromism to construct efficient photochromic materials is still an urgent necessity. Herein, we designed and synthesized a new gated photoswitching DTEP based on a Schiff base with a diarylethene core. The photochromic properties of compound DTEP can be regulated to different degrees by multiple stimuli, including UV/visible light, Cu 2+ and Ni 2+ . The compound DTEP showed different response abilities to Cu 2+ and Ni 2+, due to the diverse complexation modes between DTEP and Cu 2+ as well as Ni 2+ . The photochromic properties of compound DTEP could be inhibited completely by the introduction of Cu 2+ to form a 1 : 1 complexation, while the weak gated photochromism could be found from the DTEP –Ni 2+ complex in a 1 : 2 stoichiometry. Relying on such varying degrees of gated photochromic properties, a new molecular logic circuit was constructed to undertake complicated logical operations.